An influence of extreme southern hemisphere cold surges on the North Atlantic Subtropical High through a shallow atmospheric circulation. Issue 19 (5th October 2017) - Bowerman, A. R.; Fu, R.; Yin, L.; Fernando, D. N.; Arias, P. A.; Dickinson, R. E.
Abstract: Previous studies have attributed interhemisphere influences of the atmosphere to the latitudinal propagation of planetary waves crossing the equator, to the triggering of equatorial Kelvin waves, or to monsoonal circulation. Over the American‐Atlantic sector, such cross‐equatorial influences rarely occur during boreal summer due to unfavorable atmospheric conditions. We have observed that an alternative mechanism provides an interhemisphere influence. When episodes of extreme cold surges and upper tropospheric westerly winds occur concurrently over southern hemisphere Amazonia, cold surges from extratropical South America can penetrate deep into southern Amazonia. Although they do not appear to influence upper tropospheric circulation of the northern hemisphere, extremely strong southerly cross‐equatorial advection (>2 σ standard deviations, or 2) of cold and dense air in the lower troposphere can reach as least 10°N. Such cold advection increases the northward cross‐equatorial pressure gradient in the lower to middle troposphere, thus shallow northerly return flow below 500 hPa. This return flow and the strong lower tropospheric southerly cross‐equatorial flow form an anomalous shallow meridional circulation spanning from southern Amazonia to the subtropical North Atlantic, with increased geopotential height anomalies exceeding +1 σ to at least 18°N. It projects onto the southern edge of the North Atlantic Subtropical High (NASH), increasing its pressure and leading to equatorward expansion of NASH's southern boundary. These anomalies enhance the NASH, leading to its equatorward expansion. These extreme cold surges can potentially improving the predictability of weather patterns of the tropical and subtropical Atlantic, including the variability of the NASH's southern edge. Key Points: Cold surges from extratropical South America can influence lower tropospheric circulation over subtropical North Atlantic in June–August An anomalous cross‐equatorial shallow circulation induced by the low‐tropospheric temperature gradient is responsible for such an influence Weak upper tropospheric westerlies over the southern Amazon are required to allow deep penetration of the cold surges into the Amazon